Maternal Parenting Style and Depression in Adolescents with Divorced Parents: The Mediating Roles of Cognitive Triad and Emotion Regulation Difficulties - Dianovinina, Ktut; Surjaningrum, Endang Retno; Wulandari, Primatia Yogi (Universitas Ahmad Dahlan, 2025)
Parental divorce is one of the factors that influences depression in adolescents. It is necessary to examine the mechanisms that cause depression in adolescents from divorced families. Several studies have examined the impact of negative parenting on adolescent depression through cognitive factors and emotional regulation. However, none have investigated both factors simultaneously. This study addressed this research gap by examining the influence of maternal rejection and maternal psychological control on depression in adolescents from divorced family through the cognitive triad and emotional regulation difficulties. Respondents in this study were 227 adolescents, both boys and girls, aged 12-19 years, who had experienced their parents' divorce, and lived with their mothers. Respondents completed the Children’s Depression Inventory, Psychological Control Scale-Youth Self Report, Children-Parenting Acceptance-Rejection Questionnaire, Cognitive Triad Inventory-Children, and Difficulties Emotion Regulation Scale. Multivariate path analysis was used to examine the relationships between the study variables. The structural model demonstrated an adequate fit, χ²(df=2)=5.298, p=0.071, CFI=0.994, TLI=0.968, RMSEA=0.084 (90% CI [0.00, 0.18]), and SRMR=0.041. Maternal rejection was found to influence depression primarily indirectly through the cognitive triad (β_ind=0.215, 95%CI [0.15, 0.28]), whereas maternal psychological control was indirectly associated with depression via emotion regulation difficulties (β_ind=0.08, 95%CI [0.04, 0.12]). The model accounted for 60.5% of the variance in depression. These findings underscore the importance of cognitive-based interventions in the context of maternal rejection and emotion regulation training in the context of maternal psychological control.The findings of this study can help develop intervention programs for adolescents and parents in the context of divorced families and various related parties. This study offers findings that can be implemented in future studies.